The impact of demographics and positioning on the imaging features of the optic nerve sheath and ophthalmic vessels - David Berhanu; Luís Abegão Pinto; Inês Carneiro; Isabel Fragata; Joana Tavares Ferreira; Lia Lucas Neto (The Ultrasound Journal)
Abstract Background There are significant discrepancies in the optic nerve sheath diameter (ONSD) reported in the literature. We aimed to determine the ultrasonographic imaging features of ONSD and ophthalmic vessels in a healthy population, using a standardized protocol, and to estimate the effect of demographics and positioning changes on imaging measurements. Methods We measured the mean values of the ONSD in supine and sitting position and the Doppler imaging parameters of the ophthalmic, central retinal and short posterior ciliary arteries. Inter-observer reliability was assessed using intraclass correlation coefficient (ICC). Linear regression models were fitted to predict the effect of demographic and clinical determinants on the imaging features. Results A total of 50 measurements were obtained for each observer. The mean ONSD was 5.9 mm and there was a mean reduction of 0.2 mm when assessed in sitting position (p < 0.001). Doppler analysis showed higher peak-systolic velocity and resistive index in the ophthalmic artery (35.6 cm/s vs. 12.0 cm/s; 0.78 vs. 0.70) compared to the central retinal artery (p < 0.001). Age, sex, heart rate and systolic blood pressure were significant determinants of the imaging features, with ONSD being larger in males (p < 0.001) and increasing with heart rate (p = 0.001). ICC estimates indicated ‘good’ inter-observer reliability of the ONSD and the ophthalmic and central retinal arteries velocities and resistance. Conclusions Our findings suggest a significant impact of patient demographics and positioning during ultrasonography on the normal imaging features of the ONSD and ophthalmic vessels. The heterogeneity in methodology and clinical cohorts may justify previous discrepancies in the literature. These findings can assist in the interpretation of imaging features in clinical settings and in the standardization of point of care ONSD ultrasonography.